Cotylegaleatidae, a new family of Ploima (Rotifera: Monogononta), for Cotylegaleata perplexa gen. et sp. nov., from freshwater benthos of Belgium - de Smet, Willem H. (Zootaxa, 2007)
A new monotypic rotifer family, Cotylegaleatidae, is proposed for Cotylegaleata perplexa gen. et sp. nov., collected from benthos of an artificial small freshwater lake in Belgium. The new family belongs to the subclass Monogononta, order Ploima. Its distinctive characters include: a hollow cup-shaped structure (sucker ?) surrounding the mouth opening, a non-retractile head shield, a distal foot pseudosegment with two toes and two ventro-lateral spurs, a J-shaped vitellarium, and characteristic specialized virgate trophi with stiletto-shaped epipharyngeal elements.